Nephroblastoma in a Common Mudpuppy Necturus maculosus simultaneously Present with a Mollicute Bacterium of the Genus Acholeplasma. Issue 1 (6th April 2021) - Standish, Isaac; Leis, Eric; Erickson, Sara; Katona, Ryan; Baumgartner, Wes; Hanson, Kevin; Ibrahim, Iman; Goldberg, Tony
Abstract: In March 2017, a wild‐caught female common mudpuppy Necturus maculosus from Iowa, USA, with an enlarged posterior abdomen was submitted for diagnostic assessment. The cause of the abdominal distension was a large fluid‐filled abdominal mass, diagnosed as a nephroblastoma. Parasites and numerous bacteria were isolated and identified from the mudpuppy but were determined to be incidental. Samples of the neoplasm inoculated onto an American toad Anaxyrus americanus cell line (BufoTad) yielded cytopathic effect during several passages. However, standard molecular testing of the cell culture supernatant failed to identify any viruses. Next‐generation sequencing identified the replicating agent as a bacterium of the genus Acholeplasma . Immunohistochemistry confirmed the presence of Acholeplasma within the nephroblastoma, including within tumor cells. This is the first report of nephroblastoma and the second report of neoplasia in this species. The results also suggest that certain bacteria of the genus Acholeplasma might be oncogenic.